Left Ventricular Volume Unloading with Axial and Centrifugal Rotary Blood Pumps. Issue 3 (May 2015) - Giridharan, Guruprasad A.; Koenig, Steven C.; Soucy, Kevin G.; Choi, Young; Pirbodaghi, Tohid; Bartoli, Carlo R.; Monreal, Gretel; Sobieski, Michael A.; Schumer, Erin; Cheng, Allen; Slaughter, Mark S.
Abstract : Axial (AX) and centrifugal (CFG) rotary blood pumps have gained clinical acceptance for the treatment of advanced heart failure. Differences between AX and CFG designs and mechanism of blood flow delivery may offer clinical advantages. In this study, pump characteristics, and acute physiologic responses during support with AX (HeartMate II) and CFG (HVAD) left ventricular assist devices (LVAD) were investigated in mock loop and chronic ischemic heart failure bovine models. In the mock loop model, pump performance was characterized over a range of pump speeds (HeartMate II: 7, 000–11, 000 rpm, HVAD: 2, 000–3, 600 rpm) and fluid viscosities (2.7 cP, 3.2 cP, 3.7 cP). In the ischemic heart failure bovine model, hemodynamics, echocardiography, and end-organ perfusion were investigated. CFG LVAD had a flatter HQ curve, required less power, and had a more linear flow estimation relation than AX LVAD. The flow estimation error for the AX LVAD (±0.9 L/min at 2.7 cP, ±0.7 L/min at 3.2 cP, ±0.8 L/min at 3.7 cP) was higher than the CFG LVAD (±0.5 L/min at 2.7 cP, ±0.2 L/min at 3.2 cP, ±0.5 L/min at 3.7 cP). No differences in acute hemodynamics, echocardiography, or end-organ perfusion between AX and CFG LVAD over a wide range of support were statistically discernible. These findings suggest no pronounced acute differences in LV volume unloading between AX and CFG LVAD.